NATIVEPHILIA AND ANGLOPHILIA IN SHARMAN ALEXIE’S RESERVATION BLUES - Juliyanti Sidabutar (Muse: Jurnal of Art, 2025)
This study discusses the adverse effects of foreign cultural influences on local cultures and the repercussions faced by local cultures that adopt foreign elements. Utilizing a qualitative methodology, the research draws on primary data from Sherman Alexie's novel Reservation Blues (1995) and various scholarly articles relevant to the themes explored. The analysis is framed within two postcolonial theories proposed by Homi Bhabha and Tressa Berman, which provide distinct perspectives on identity and representation in a postcolonial context, specifically focusing on the concepts of nativephilia and anglophilia, closely linked to cultural appropriation and mimicry. The findings indicate that 1) Cultural appropriation contributes to the erosion of local customs and the loss of cultural heritage, highlighting the risks associated with the uncritical adoption of foreign cultural practices. 2) Mimicry leads to negative consequences for individuals and society, ing a sense of alienation and disconnection from one's cultural identity.